The Analisis Biaya Produksi Terhadap Pendapatan Petani - Yuliana; Sudiyarti, Nining; Rachman, Rosyidah; Sutrisno, Eko; Rahayu, Sri (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The agricultural sector can have the ability to produce a surplus, this happens when productivity is increased so that it produces higher farmer income. The increase in the standard of living is obtained by increasing food products either through intensification, extensification and diversification of agriculture which is expected to improve the standard of living of farmers, expand employment opportunities for groups of people who still depend on the agricultural sector. The purpose of this study was to analyze production costs on the income of rice farmers in Bagetango Hamlet, Lopok District, Sumbawa. Quantitative research methods were used in this study, through multiple linear regression tests, production costs in this study include land area, seeds, fertilizers, pesticides, and labor, with the help of the Statistical Package for the Social Sciences (SPSS), based on the objectives to be achieved, this study uses the income of rice farmers in Bagetango Hamlet, can be achieved with the average production of each respondent then multiplied by the selling price of production to obtain total income. The results of the study showed that the influence of production costs on farmer income is very significant. If production costs are too high without being balanced with adequate results or good prices, farmer income will decrease. Therefore, to increase income, farmers need to manage production costs wisely, utilize technology, and monitor changes in market prices.